"There Is No (Where a) Face Like Home": Recognition and Appraisal Responses to Masked Facial Dialects of Emotion in Four Different National Cultures. (December 2021) - Tsikandilakis, Myron; Yu, Zhaoliang; Kausel, Leonie; Boncompte, Gonzalo; Lanfranco, Renzo C.; Oxner, Matt; Bali, Persefoni; Urale Leong, Poutasi; Qing, Man; Paterakis, George; Caci, Salvatore; Milbank, Alison; et al.
The theory of universal emotions suggests that certain emotions such as fear, anger, disgust, sadness, surprise and happiness can be encountered cross-culturally. These emotions are expressed using specific facial movements that enable human communication. More recently, theoretical and empirical models have been used to propose that universal emotions could be expressed via discretely different facial movements in different cultures due to the non-convergent social evolution that takes place in different geographical areas. This has prompted the consideration that own-culture emotional faces have distinct evolutionary important sociobiological value and can be processed automatically, and without conscious awareness. In this paper, we tested this hypothesis using backward masking. We showed, in two different experiments per country of origin, to participants in Britain, Chile, New Zealand and Singapore, backward masked own and other-culture emotional faces. We assessed detection and recognition performance, and self-reports for emotionality and familiarity. We presented thorough cross-cultural experimental evidence that when using Bayesian assessment of non-parametric receiver operating characteristics and hit-versus-miss detection and recognition response analyses, masked faces showing own cultural dialects of emotion were rated higher for emotionality and familiarity compared to other-culture emotional faces and that this effect involved conscious awareness.